La garantie autonome ou lettre de garantie en droit OHADA - Wathie, Diegoye (Marmara Üniversitesi Hukuk Fakültesi Hukuk Araştırmaları Dergisi, 2016)
OHADA’da benimsenmiş terminolojiye göre teminat mektubu olarak anılan bağımsız garanti, teminat hukuku alanındaki önemli yeniliklerden biridir. Teminat mektubunun sözleşmesel nitelik taşımakta olduğu Yeknesak Belge’deki tanımda açıkça ortaya koyulmuştur, fakat revizyon söz konusu tanımı taahhüt kavramından bahsetmek suretiyle tartışmaya açık hale getirmektedir. Teminat mektubunun çeşitli şekli koşullara uyması gerekmektedir; bu koşullara uyulmaması geçersizliğe sebep olur. Teminat mektubu ile yalnızca tüzel kişiler borç altına girebilir, gerçek kişilerin teminat mektubu vermesi mümkün değildir. Teminat mektubunun özellikleri arasında bağımsız olması ve defi ileri sürmenin mümkün olmaması bulunmaktadır. Yeknesak Belge teminatın süresini sınırlamaktadır. Ancak belgenin revize edilmiş halinde süresiz teminat verme olanağı getirilmiştir. Talimat veren hile veya kötüye kullanma durumunda ödeme yapmama imkanına sahiptir. Bu koruma çerçevesinde, garanti veren ve kontrgarantör de talimat veren gibi rücu imkanına sahiptir. Rücu kişisel olabileceği gibi halefiyete de dayanabilir.
Number: 3 Autonomus Warranty or Letter of Guarantee in OHADA Law
Keywords: Autonomous guarantee; Bağımsız garanti; Letter of guarantee; OHADA; Tek Hukuk; Teminat; Teminat mektubu; Uniform Act; Warranty

Apport des Instruments de la Conférence de La Haye au droit des affaires dans l’espace OHADA - Monsenepwo Mwakwaye, Justin (Junges Afrikazentrum, 2016)
doi:10.25972/OPUS-14102

La protection internationale des investissements en République démocratique du Congo à l’aune de l’affaire Patrick Mitchell devant le Centre International pour le Règlement des Différends relatifs aux Investissements (CIRDI) - Djuma Bilali, Lokema Guy-Prosper (KAS African Law Study Library, 2016)

Le contrôle bancaire au regard des enjeux actuels des activités des banques privées en RDC – Entre la protection des clients, l’encouragement et la promotion des banques et la sécurité de l’Etat - Nsambana Bonkako, Juslain (KAS African Law Study Library, 2016)
Keywords: Banque; Banque privée; Client (protection); Contrôle bancaire; Promotion; RDC; Sécurité

Affaire Unilever.droit de travailleurs dans les sociétés étrangères - Nsomwe, Stéphanie (KAS African Law Study Library, 2016)

The stakeholder theory of corporate control and the place of ethics in OHADA: The case of Cameroon - Sama-Lang, Irene; Zesung, Njonguo Abel (African Journal of Business Ethics, 2016)
The rapid increase in globalization in the last two and a half decades has caused businesses to easily transcend national boundaries. States respond to such flexibility by harmonising their laws to easily adapt to such changes in order to attract investments. This is the case with the OHADA jurisdiction where its architects foresaw an economic spur through integration of business laws. Though expected to stay within the bounds of the law, the law cannot absolutely determine how businesses should prioritise their stakes. As such, ethics comes in to complement the law. This article uses the stakeholder theory of corporate control to investigate the place of ethics in OHADA, as applied in Cameroon. It concludes that an altruistic social conscience is still highly wanting.
Keywords: Business; Corporate control; Corporate law; Ethics; OHADA; stakeholder

Tax Mobilization in Sub-Saharan Africa: The Impact of Tax and Business Law Reforms - Bertinelli, Luisito; Bourgain, Arnaud (Economics Bulletin, 2016)
This paper contributes to measuring the influence of business (and tax) law reforms on sub-Saharan African countries tax mobilization ability. Relying on a new business law reform indicator, our results validate the significant impact of corporate law modernization on governmental revenue, and unearth a complementary effect between business and tax law reforms.

The United Nations Convention on the Use of Electronic Communications in International Contracts at Ten: Practical Relevance and Lessons Learned - Castellani, Luca G. (Journal of Law, Society and Development, 2016)
The United Nations Commission on International Trade Law prepared the first global treaty specifically devoted to electronic commerce law, the United Nations Convention on the Use of Electronic Communications in International Contracts. That treaty builds on the highly successful UNCITRAL Model Law on Electronic Commerce and the UNCITRAL Model Law on Electronic Signatures. This article describes the main goals of the Electronic Communications Convention and its scope of application. In particular, it illustrates how that Convention may fully enable the use of electronic means under other widely adopted treaties such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards and the United Nations Convention on Contracts for the International Sale of Goods. The article also describes the main substantive provisions of the Electronic Communications Convention, in particular clarifying how that Convention updates and completes the provisions of the UNCITRAL Model Law on Electronic Commerce. This Model Law is the backbone of electronic commerce law in numerous countries and a de facto legislative standard insouthern Africa. Finally, the article describes the manner (or patterns) in which the adoption of the Electronic Communications Convention takes place. It stresses that, while the Convention is often used as a source of inspiration for domestic law reform, in order for it to achieve all its intended goals, its formal adoption as a treaty is necessary. The final message is therefore a call upon all states to consider the adoption of that Convention in order to support the broader use of electronic means, especially in the light of the implications for economic development and the promotion of paperless trade.
Keywords: Convention adoption patterns; Digital signatures; Electronic communications; Electronic contracting; Legal harmonisation

Force Majeure, Change of Circumstances and Termination of Contract - Han, Shiyuan (Journal of Law, Society and Development, 2016)
It is impossible to draw a distinct line between force majeure and change of circumstances, because the two overlap. In order to regulate both force majeure and change of circumstances, the United Nations Convention on Contracts for the International Sale of Goods (CISG) has adopted a unified model in article 79, whereas Chinese law adopts a dual model by treating them as different things and regulating them in different articles. Where the purpose of a contract becomes impossible to achieve because of a force majeure and both the CISG and Chinese Contract Law (the CCL) adopt the same model of termination of the contract, the contract should be terminated by one party with a notice to the other party instead of ipso facto avoidance. In a case of a change of circumstances, in order to terminate the contract, both the CISG and the CCL actually follow the path of raising an action by a notice of avoidance or termination to theother party. Both approaches have their merits and demerits but the differences between them in practice are not as large as presumed. Where force majeure and change of circumstances overlap each other, possible ways for termination of the contract are for a party either to choose their preferred solution or to follow the lex specialis derogat generali. The latter way is preferred in this article; and while in an action for termination the judge may balance the interests of both parties in making a final decision, the uniform application of the law, the safety of the transaction and the fairness of the judgment may be ensured in so doing.
Keywords: CISG; Change of circumstances; Chinese Contract Law; Force majeure; Gestaltungsklagerecht; Termination

Oil in the Gulf of Guinea States and South Africa in the Matrix of Overlapping Membership of African Regional Communities: An Impediment to Regional Integration? - Jobodwana, Zingisile Ntozintle (Journal of Law, Society and Development, 2016)
The Gulf of Guinea states (GOGs) discussed in this article comprise a diverse group of more than 20 African states bordering on the oil-rich Gulf of Guinea. They are former colonies of Belgium, France, Great Britain and Germany. These states are of strategic importance to the United States, the European Union, India and China because of their tremendous natural resources that include biodiversity, oil, gas and other strategic minerals. But to what extent are they also of strategic importance not only to South Africa but to SADC member states? After all, the GOGs boast of their sea routes being safer and more convenient for sea transport. Post-colonial independence finds these states still adopting a mixture of foreign legal systems side by side with indigenous laws and customs. The region is still underdeveloped, with poor physical infrastructure, weak government structures, an inefficient legal system, and internecine strife and other inter-state disputes exerting a debilitating influence. The NEPAD Plan of Action of 2001 looks to the regional economic communities (RECs) to become the leaders in regional economic co-operation and integration. Although the GOGs are characterised at present by overlapping membership of various communities, they have enjoyed some successes based on the newly found petroleum commodity which, wisely managed, can help to increase intra-African trade and produce a viable extensive African market buttressed by South Africa's economic advances into the rest of Africa. In some of the regions in Africa RECs such as ECOWAS and SADC have been able to transform their economic and monetary co-operation efforts into a powerful driving force for economic policy co-ordination and integration, but a strong, credible, effective and efficient legal framework with sustainable supporting institutions is now needed. South Africa is well poised to assist with deepening the political and economic integration in the GOGs by intensifying foreign direct investment (FDI), capacity-building and training projects, and the transfer of skills and technology. But the RECs overlapping membership needs to be rationalised, the negative influences of the superpowers need to be resisted, and support is required to maintain peace and stability and ensure the security of the maritime regimes. A strong, independent supra-national body that is also able to supervise and monitor revenues from oil for the benefit of the region as a whole should be established.
Keywords: African Union; COMESA; EAC; ECCAS; ECOWAS; Gulf of Guinea Commission; Gulf of Guinea states; OHADA; Overlapping membership; Regional economic communities (RECs); Regional integration; SACU; SADC; South Africa; Supra-national independent regiona; Treaties

The Attitude of OHADA Law Countries Towards the CISG - Kahindo, Nguru Aristide (Journal of Law, Society and Development, 2016)
Disparities in national laws are likely to result in uncertainty which, in turn, creates obstacles to international commerce. It is acknowledged that strong investment flows cannot be achieved without a secure legal and commercial environment. Mindful of such a need, states decided to harmonise sales law internationally. To this end, in 1980 they adopted the United Nations Convention on Contracts for the International Sale of Goods known as the Vienna Sales Convention or the CISG. The CISG has led a number of countries, including the Organisation for the Harmonisation of Business Law in Africa (OHADA) law states, to modernise their local sales law. However, only three of 17 countries that constitute the OHADA community have ratified the CISG. OHADA law countries give the impression of favouring a more regional approach to the unification of sales law rather than the CISG™s global approach by implementing a local Commercial Uniform Act. Their indifference towards the CISG is not without consequences for commerce in the OHADA region. This article seeks to demonstrate that the lack of ratification of a universal convention, as for example the CISG, poses a danger to commercial dealings. It also intends to show that the CISG is not hostile to regional uniform sales laws of the OHADA Commercial Uniform Act type. It concludes that OHADA countries do not need to be afraid of their acceptance of the CISG and recommends that it be ratified.
Keywords: Business law; CISG; Commercial Uniform Act; Harmonisation; OHADA law; Uniform sales law

The UNCITRAL Model Law on International Commercial Arbitration: Interpretation, General Principles and Arbitrability - Viscasillas, Pilar Perales (Journal of Law, Society and Development, 2016)
This article explores the possible modification of the UNCITRAL Model Law on International Commercial Arbitration (MAL) to include the topic of arbitrability. This is an area in which the domestic legal systems differ, particularly in relation to the arbitrability of intra-corporate disputes. The article also deals with new art 2A, introduced into the Model Law in 2006, which deals with the interpretation and gap-filling system under the Model Law. The interpretation of MAL in accordance with its international character is a very important step towards uniformity and therefore the different tools required for a uniform interpretation are analysed. These include case law and scholarly writings; the meaning and importance of achieving both a uniform and an international interpretation of MAL are also considered. The article also analyses the whole text of MAL in order to arrive at the general principles on which the Model Law is based; when problems have to be solved, these principles should guide issues of interpretation that arise under this law.
Keywords: Arbitrability; Arbitration; General principles; Interpretation; UNCITRAL

Regional Harmonisation of Contract Law - Is It Feasible? - Zeller, Bruno (Journal of Law, Society and Development, 2016)
This article investigates whether regional harmonisation is merely an academic exercise or a serious attempt to create a uniform contract law in a defined region. It builds on the recently conducted Symposium at Villanova University in 2013 and addresses comparatively the efforts by well-defined regions, namely OHADA, the EU and ASEAN. OHADA has introduced regional uniform laws; the EU is still working on formulating them. Furthermore, UNCITRAL has considered a proposal by the Swiss government to work urgently on a new initiative to further harmonise contract law. Against this backdrop, this article argues that regional proposals to harmonise contract law are akin to saying that ‘ein Gespenst geht um’ (a ghost is going around) (Reich 2006: 425). This is justified, because a proposal to create a harmonised contract law in East Asia has currently also been discussed, but the discussions have stalled. Is there a solution or do we simply admit that regional harmonisation is not possible? The starting point is the CISG, as has been adopted by 80 countries and needs to be considered by any region as a possible, albeit not perfect, solution. If the CISG has already been ratified, the issue, then, is how any regional developments can coexist with it. Or does a ratification of the CISG preclude any regional harmonisation? Secondly, the question must be asked whether regional harmonisation will reduce transaction costs, which is beyond what the CISG was able to achieve. This article argues that as far as the drafting of international instruments isconcerned, a shift in thinking has occurred. Instruments such as the Cape Town Convention are considered to be reforming the law in a particular narrow area rather than attempting to draft codes. Furthermore, the process is driven by industry groups. Regional harmonisation must take note of the ongoing shift and a more fruitful approach is to develop uniform laws through a better understanding and coordination of existing instruments.
Keywords: CISG; Contract law; Regional harmonisation; Uniform law

Arbitrability and public policy: an African perspective. - Mante, Joseph (Arbitration international, 2016)
Growth in international trade has led to considerable expansion of the scope of matters capable of settlement by arbitration. In spite of sustained scholarly activity on arbitrability, the question of what is arbitrable remains controversial but relevant in many regions of the world, including Africa. Arbitrability has the potential to affect the validity of an arbitration agreement, strip an arbitrator of jurisdiction, or derail enforcement of an award. Given the significance of the concept, it is vital that entities involved in international transactions do not speciously extrapolate knowledge of what pertains in Europe and America across all jurisdictions and regions of the world. This study draws a comparison between arbitrability and its relationship with public policy in Europe and America on one hand, and the trend in Africa in an attempt to critically investigate the extent to which African states are willing to extend the scope of arbitrable subject matters. A number of trends on arbitrability are discernible. Most commercial disputes are arbitrable and this observation generally aligns with practice in Europe and America. Beyond this, there are three significant differences in the areas of scope of subject matter, approaches to arbitrability regulation and the role of public policy.
https://rgu-repository.worktribe.com/output/246435/arbitrability-and-public-policy-an-african-perspective
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Policy

Plaidoyer pour l’adoption du crédit-bail en Afrique en droit OHADA - Pohé Tokpa, Denis (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2016)
Il s’agit de revêtir le manteau du législateur africain pour rechercher le profil idéal de l’un des contrats d’affaires le plus utilisé aujourd’hui dans la pratique en Afrique mais sans faire forcément l’objet d’une réglementation adaptée. Lors de la dernière conférence des chefs d’Etat des pays membres de l’OHADA au Burkina Faso en janvier 2014, le crédit-bail a été retenu entre autres contrats d’affaires comme l’un des principaux axes d’un projet d’Acte uniforme. Dans les pays d’Afrique où l’épargne locale est quasi-inexistante, le crédit- bail est un moyen incontournable pour les TPE et PME disposant de très peu de fonds propres et qui ont difficilement accès au crédit bancaire, faute de garanties suffisantes, pour développer leur activité économique.

Assessment of Compliance with OHADA Uniform Accounting Act by Public Limited Companies - Fossung, Michael Forzeh (Accounting and Finance Research, 2016)
Francophone African countries have made a tremendous effort in harmonising domestic standards and reporting with the International Financial Reporting Standards (IFRS). Moving from two distinct OCAM streams to two OHADA streams (effective 1985) and now one OHADA Uniform Accounting Act embodying 17 member countries (effective 2001) is a milestone towards harmonisation of reporting practice both domestically and internationally. This empirical study examines whether the effort of harmonisation, especially after the 2001 standards has resulted in the successful convergence of firms' accounting practices by analysing public limited liability companies' compliance with the OHADA Uniform Accounting Act and if such compliance has improved over time. The study has been carried out using the 2008 and 2009 annual reports of three public limited companies in the OHADA zone that translate their financial statements into IFRS. The ranks of closeness and compliance index have been used to analyse data. Findings reveal a relatively high level of compliance with the accounting regulation by sampling limited liability companies. The results also give an indication of harmonisation in accounting practice of limited companies within member countries as they were found to be substantially consistent in compliance, especially in countries that have instituted the Statistics and Tax returns (or "DSF") as a reporting medium.
Number: 3

Convention de l’Union africaine sur la cybersécurité : plaidoyer pour un dépassement des traditions - Kablan, Serge; Oulai, Arthur; Sanni Yaya, Mouhamadou (Revue de droit des affaires internationales, 2016)
« Au commencement était l’Afrique ». Cette évocation, que continuent d’étayer les découvertes successives de fossiles d’Australopithèques, est à la Commission de l’Union africaine l’indication des origines temporelle et géographique de « l’immense aventure humaine du progrès ». Le continent, tout autant exposé aux phases contemporaines de l’équipée, entendues particulièrement des développements technologiques, a engagé plusieurs initiatives d’accompagnement dont l’une des plus récentes, promue par l’Union africaine, vise à doter ses 54 États membres d’une convention instituant un cadre juridique de confiance pour la cybersécurité. Il y a, dans cette convention, l’ambition triple d’organiser les transactions électroniques, d’assurer la protection des données à caractère personnel et de lutter contre la cybercriminalité. D’un point de vue prospectif, les auteurs apprécient l’effectivité de la convention eu égard à la question spécifique du commerce électronique, en tentant de déterminer si, dans sa forme comme dans sa substance, cet instrument a les moyens de satisfaire aux préoccupations de sécurité juridique et technique des différents milieux concernés.

A mediação incidental como meio de solução dos conflitos trabalhistas individuais: a questão da dispensa de trabalhadores detentores da garantia provisória no emprego - Santos, Ricardo Goretti; Leite, Carlos Henrique Bezerra (Espaço Jurídico Journal of Law, 2016)
Resumo: Este artigo versa sobre a prática da mediação incidental no processo do trabalho e sua potencial contribuição para a efetiva solução de conflitos decorrentes da dispensa de trabalhadores dotados de garantia provisória do emprego. Acusa o uso desordenado da conciliação incidental, indiscriminadamente aplicada na solução de conflitos individuais situados no âmbito de relações trabalhistas, tanto circunstanciais quanto continuadas. Busca responder ao seguinte problema de pesquisa: a prática da mediação judicial incidental na Justiça do Trabalho pode contribuir para a efetiva solução de conflitos decorrentes da dispensa do trabalhador dotado de garantia provisória do emprego? Estabelece as bases do fenômeno da difusão dos métodos alternativos de solução de conflitos, no contexto do movimento universal de acesso à justiça. Desenvolve considerações sobre particularidades da conciliação e da mediação, destacando os aspectos principais de distinção entre elas. Finalmente, avalia a aplicação dos métodos autocompositivos, considerando as particularidades das controvérsias decorrentes da dispensa de trabalhadores dotados de garantia provisória no emprego. Conclui que, por objetivar a exploração aprofundada dos interesses em jogo, o fortalecimento do diálogo e da relação entre as partes, além do empoderamento dos envolvidos, a mediação judicial incidental seria a via mais adequada para a administração de conflitos decorrentes da dispensa de trabalhadores com garantia provisória do emprego. Além isso, evidencia uma proposição legislativa sobre o tema, já submetida à apreciação da Comissão de Juristas responsável pela elaboração do Anteprojeto de Lei de Arbitragem e Mediação, do Senado Federal.
Incidental mediation as a means of solving individual labor disputes: the issue of dismissal of employees holding a provisional guarantee of employment
Keywords: Arbitrage (droit du travail); Arbitragem; Arbitration; Conciliation (droit du travail); Conciliação trabalhista; Despedida arbitrária; Garantia no emprego; Labour dispute; Mediation; Mediação trabalhista; Médiation; Resolução alternativa de conflitos

L’arbitrage en droit espagnol des sociétés, à l’aune du droit comparé - Correa Delcasso, Jean-Paul (La Lettre, 2016)
Dans la présente étude, l’auteur expose l’évolution qu’a connue la pratique de l’arbitrage en droit espagnol depuis ses débuts. Il analyse, d’un point de vue pratique, les principales solutions dégagées par la jurisprudence espagnole, en ce qui concerne l’arbitrabilité d’un grand éventail de litiges, question qui s’est traditionnellement posée en droit espagnol. Il compare la situation avec celle d’autres systèmes juridiques européens culturellement proches.

Admission de la question préjudicielle posée par le juge de l’annulation de la sentence - Posocco, Laurent (La Lettre, 2016)
Le juge de l’annulation de la sentence arbitrale internationale a la faculté de demander à la Cour de justice de l’Union européenne (CJUE) de statuer sur une question d’interprétation du Traité sur le fonctionnement de l’Union Européenne (TFUE) en vertu de son art. 267.

Bonne foi de l’avocat dans la mise en œuvre de la clause compromissoire - Posocco, Laurent (La Lettre, 2016)
Ayant fait ressortir que les parties avaient eu la volonté de se soumettre à l’arbitrage, l’exigence de bonne foi pouvait leur être opposée et que les pouvoirs du cabinet d’avocats émirati étant apparents, la croyance de la société d’avocats londonienne mandatée à l’engagement des parties était légitime, la cour d’appel en a exactement déduit que le tribunal arbitral était compétent.

La responsabilité de l’arbitre et son assurance - Raibaut, Jacques (La Lettre, 2016)
La figure de l’arbitre, comme celle du juge, paraît étrangère à la responsabilité tant domine l’image de la fonction recherchée par le justiciable : dénouer le conflit qui les oppose. Au-delà de la déception que peut susciter la décision rendue chacun admet que l’indépendance, l’impartialité et la compétence sont inhérents à cette fonction et justifient que l’arbitre bénéficie d’une immunité juridictionnelle de principe qui le met à l’abri du ressentiment d’une ou des parties.

An Introduction and an Evaluation of Arbitration in Ivory Coast - Kalle, Aurélie (Recht in Afrika, 2016)
The paper deals with arbitration law in Ivory Coast and is mainly based on interviews with the most important authorities in this field. After a short introduction into the OHADA legal system the two main arbitration centres of Ivory Coast are presented. First, the paper treats the internationally known OHADA arbitration centre of the Common Court of Justice and Arbitration, hereinafter known as CCJA. It explains the bodies and the organisation of the CCJA, the arbitration procedure in detail, the enforcement of the arbitral award, the interim measures and the legal remedies against decisions of the CCJA. Second, the functioning of the Court of Arbitration of Côte d'Ivoire, hereinafter known as CACI, is explained. It is the second arbitration centre of Ivory Coast and it was created by the Ivorian Chamber of Industry and Commerce and settles mainly disputes between nationals. The analysis treats the same topics as mentioned for the CCJA centre, but is restricted to point out the differences or peculiarities of the CACI procedure, in order to prevent repetitions. Third, the paper analyses the advantages and disadvantages of the two arbitration centres and compares them to the proceedings of the Commercial Court of Abidjan. It avoids the comparison of yet well-known arguments such as confidentiality of arbitration proceedings or the parties' free choice in regard to the place of arbitration and the language, etc. The work rather limits itself to concretely address the problems or the advantages of each dispute solution considering the latest developments in the judicial system. The purpose of the report is to give a practical introduction into the Ivorian arbitration law, in particular to foreign lawyers. It should provide them with solid theoretical knowledge of the different dispute solutions. With the help of concrete comparisons and explanations of the actual situation regarding the civil and commercial judicial system it should enable them to find the most suitable dispute solution for their clients.
Keywords: Arbitrage; Arbitragem; Arbitration; Côte d'Ivoire; Ivory Coast

Integration through comparative private law: Four lessons from Cappelletti - Infantino, Marta (International Journal of Constitutional Law, 2016)
The aim of this article is to explore Cappelletti’s most enduring teachings relevant to those who promote global or regional integration of private laws. The article will review Cappelletti’s insights into the dynamic history of law, the need to respect diversity and take into account society’s imbalances, and the duty of comparative lawyers to engage in “applied” interdisciplinary legal research.

Les conflits d'intérêts : aspects de gouvernance - Trochon, Jean-Yves (Cahiers de droit de l'entreprise, 2016)

CSR and financial performance parameters of DBBL: An empirical analysis - Farijul, Islam; Rahman, Mostafizur (International Journal of Innovation and Scientific Research, 2016)
The purpose of the current study is to show the statistical linkage between CSR expenditure of financial service firm mainly DBBL and its financial performance on the basis of some key parameters that attempts to contribute to the existing knowledge of corporate social responsibility initiatives by businesses and its ability to influence their financial performance. Consequently, the main objective is to examine the relationship between CSR and financial performance of the banking sector. For this purpose, various financial drivers are used such as EPS, DPS, NPAT, ROE, EVA ROA, MVA and, ROE and ROI. After getting all the relevant data from secondary sources like annual reports and reports from Bangladesh Bank, statistical tool like multivariate analysis in the form of Bi-variate Regression is used to depict the relationship and the developed hypotheses are tested by using Univariate analysis in the form of one sample t test under parametric test. The major finding of this study demonstrates evidence that there is a statistical significant linkage between CSR and Performance of the sample bank.
Keywords: CSR; DBBL; Financial performance parameters

Afri̇ka’da Ekonomi̇ Hukuku’nun Uyumlaştirilmasina İli̇şki̇n Sözleşme’ye (ohada Sözleşmesi̇)* Genel Bakiş - Namlı, Mert (Public and Private International Law Bulletin, 2016)
Uzun bir suredir, bircok Afrikali devlet, ulkelerine yapilan yabanci yatirimin istenilen seviyeye ulasmamasindan yakinmakta olup, bunun baslica nedeninin ise “hukuk duzen- lerindeki belirsizlik ve istikrarsiz oldugunu tespit etmislerdir. Bunun sonucunda, bolge devletlerinin hukuk duzenlerini uyumlastirma(daha dogru bir ifadeyle yeknesaklastirma) yoluyla yeni bir “birlesik hukuk” yaratilmasi bir ihtiyac olarak belirmistir. Iste bu amacla bircok Afrikali devlet, ozellikle de Frank Bolgesi devletleri, 07.10.1993 tarihinde Port- Louis’de(Mauritus) bir uluslararasi sozlesme imzalayarak Afrika’da Ekonomi Hukuku Uyumlastirilmasi Orgutu’nu (OHADA) kurmuslardir. OHADA’nin temel amaci, Afrika’da Ekonomi Hukuku alaninda modern ve uyumlu bir hukuk yaratilarak bolge devletleri ara- sinda bu alanda hukuki entegrasyonun saglanmasidir. Bu makale, Sozlesme’nin tarihsel arka planini, temel amaci ve yontemini, cografi ve maddi kapsamini, yeknesak islemlerin temel ozellikleri ve kabul edilme usulunu, OHADA’nin kurumlari olan Devlet ve Hukumet Baskanlari Konferansi, Bakanlar Konseyi, Ortak Adalet ve Tahkim Mahkemesi, Daimi Sek- reterlik ve Bolgesel Yuksek Hakimlik Okulunu (ERSUMA) ve OHADA’nin Afrika’daki diger ekonomik ve parasal birlikler arasindaki yerini an hatlariyla tanitmayi amaclamaktadir. Anahtar Kelimeler: OHADA, Afrika, Ekonomi Hukuku, hukuki entegrasyon, uluslar arasi sozlesme.
Keywords: Afrika; Ekonomi Hukuku; hukuki entegrasyon; uluslar arası sözleşme

The OHADA Common Court of Justice and Arbitration: Exogenous Forces Contributing to Its Influence - Dickerson, Claire Moore (Law and Contemporary Problems, 2016)

Reflections on the Nexus Between Public Procurement Reforms and Economic Development in Nigeria - Okolie, Aloysius-Michaels; Nnamani, Kelechi (African Journal of Politics and Administrative Studies, 2016)
Corruption has widely been recognized as one of the impediments to the socio-economic cum political development of Nigeria. By 2000, it was observed that the conduct of government business in Nigeria had become difficult and expensive due to pervasive corruption, particularly procurement fraud. Although procurement fraud is one of the most common avenues of corruption in most countries, its incidence in Nigeria by 2000 was particularly widespread. To reverse this ugly trend, the Nigerian government initiated the public procurement reforms with a view that a corrupt-free procurement process will among other things, promote economic development in the country. Consequent upon the reform, the Public Procurement Act was enacted while the Bureau of Public Procurement was established to ensure due process, accountability and transparency in the award of government contract. In this light, this study evaluated the impact of the public procurement reforms on the economic development of Nigeria. We relied on documentary method of data collection and content analysis of data. Meanwhile, employing the basic propositions emanating from the Marxist theory of the Post-Colonial State, this study noted that the nature and character of Nigerian state undermined the procurement reform from achieving its expected goals. We however, recommended for the removal of the immunity in the constitution and strengthening of the anti-graft agencies in Nigeria.
Keywords: Corruption; Economic Development; Public Procurement; Reforms; Transparency

Contrariétés entre jugements étatiques et sentences arbitrales dans l'espace OHADA - Castellane, Béatrice (Penant : revue trimestrielle de droit africain, 2016)

The Quality of External Audit in OHADA Space: A Qualitative Study with Board of Director’s Members’ Perception as Understanding Variable - Hanko, Osée (Applied Finance and Accounting, 2016)
Audit quality has been evaluated in academic literature accordingly with auditor qualities, due to the difficulties of observing auditing technical process itself. The qualities of a good auditor are then competence and independence, sine qua none conditions of audit quality. That approach is otherwise valid only if there is a valuable framework like stock market where auditor’s competence and independence could be observed. In OHADA space countries, the financial market is approximately off. It is therefore impossible to assess audit quality the way it has been done in prior literature. This study suggests a new approach of assessing audit quality in OHADA countries in relation with audit committees member’s perception of auditing process. Using an innovative qualitative approach inspired from Manita (2008), the results suggest to take into account the auditor’s knowledge of the company, the relevance of the identified zone of risks and the degree of communication with the board of directors.
Number: 2

LLCs and the Private Ordering of Dispute Resolution - Molk, Peter; Winship, Verity (The Journal of Corporation Law, 2016)
An emerging question in U.S. business law is how the organizational documents of a business entity set the rules for resolving internal disputes. This practice is routine in commercial contracts, which may specify where or how disputes must be resolved. Recent use of litigation provisions in corporation charters and bylaws have sparked controversy, ultimately leading to legislative action to preserve shareholder suits from contractual waiver. Yet despite accounting for the majority of business organizations and sharing features with corporations, non-corporate business entities and their internal dispute resolution process have been largely ignored. How do these non-corporate entities set ex ante rules for resolving disputes among their constituents? This paper begins to map this uncharted area with an empirical study of the practice of limited liability companies (LLCs). We find widespread use of contract to alter the default dispute resolution practices. This study helps not only to inform the evolving statutory and judicial framework for LLC regulation, but also to predict how corporations may respond in the future to recent judicial and legislative changes.
Keywords: Arbitration; Dispute resolution; Fee shifting; Forum; LLCs; Litigation; Operating agreements

Les orientations du législateur OHADA dans l'AUSCGIE révisé - Badji, Patrice Samuel Aristide (Revue de l'ERSUMA, 2016)
Keywords: Acte uniforme; Droit des sociétés commerciales et du GIE; Législateur; Orientations

La loi camerounaise du 10 décembre 2010 sur le crédit-bail à l'aune des législations OHADA et CEMAC - Kalieu Elongo, Yvette Rachel (Revue de l'ERSUMA, 2016)
Keywords: Crédit-bail; Loi camerounaise; Législateur CEMAC; Législateur OHADA

Le formalisme de la sasie immobilière en droit OHADA - Tsetsa, Guy Saturnin (Revue de l'ERSUMA, 2016)
Keywords: Droit OHADA; Saisie immobilière

La réforme du droit OHADA des sociétés commerciales : modernisation du droit applicable ou conformisme législatif ? - Wane, Diélya Yaya (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2016)
L’organisation pour l’harmonisation du droit des affaires (OHADA), dans le cadre de sa mission d’uniformisation du droit des affaires en Afrique, a adopté le 17 avril 1997, l’Acte uniforme portant droit des sociétés commerciales et du groupement d’intérêt économique. Ce texte a connu une réforme d’envergure entrée en vigueur le 05 mai 2014. Dans sa lettre et dans son esprit, le nouveau texte transcrit le droit positif des sociétés commerciales tel qu’il existe en France. La tendance forte chez le législateur Ohada à se conformer au droit de l’Ancienne Métropole remet cependant au goût du jour la question du mimétisme juridique, tant décriée par la doctrine. Son opportunité, notamment dans un domaine, qui, tel que le droit des sociétés commerciales, est soumis à de constantes variations, serait largement sujette à caution. De nouvelles analyses démontrent, toutefois, que, loin de réduire l’importance ou l’originalité du droit communautaire des sociétés, la question du conformisme législatif doit être envisagée sous le prisme de l’inévitable rapprochement entre les différents systèmes juridiques. Ce faisant, il devient l’indispensable acteur de la mondialisation du droit.

La nationalité des sociétés dans les pays de l'espace OHADA : les cas du Niger, du Sénégal et de la RD Congo - Abdou Assane, Zeinabou (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2016)
Le développement des relations économiques internationales et la construction d’un espace communautaire intégré d’un point de vue économique et juridique relancent le débat sur la nationalité des sociétés. La question n’est pas de démontrer s’il existe une nationalité des sociétés, puisque la doctrine et la jurisprudence ont proposé des solutions qui sont déjà acceptées ; mais d’analyser plutôt comment cette notion s’adapte aux contraintes d’une économie régionalisée voire mondialisée. Ainsi, les critères de rattachement juridique d’une société retenus par les pays de l’espace OHADA en l’occurrence le Niger, le Sénégal et la RD Congo sont analysés en vue de la détermination de la lex societatis. La notion de nationalité des sociétés dans les pays de l’espace OHADA, pose tout de même quelques difficultés liées à la multiplicité des textes notamment le droit national et le droit OHADA ainsi que les autres droits communautaires. De nombreuses conséquences découlent de la détermination de la nationalité des sociétés dans le cadre de la réglementation de leurs activités.
Keywords: Contrôle; Lex societatis; Liberté d’établissement; Nationalité; Rattachement juridique; Siège social; Société étrangère

Le nantissement des marques de produits ou de services : le législateur OHADA à l’épreuve de l’immatérialité - Bakam Titgoum, Nadine Josiane (Les Cahiers de propriété intellectuelle, 2016)
Keywords: Intellectual property; Nantissement; Propriedade intelectual; Propriété intellectuelle; Sureties; Sûretés

Revue de la jurisprudence 2015 en droit des entreprises - Bouchard, Charlaine (Revue du notariat, 2016)

Direct actions and arbitration: all at sea - Briggs, Adrian (Lloyd's Maritime and Commercial Law Quarterly, 2016)

The CISG as a Model Law: A Comparative Law Approach - Chianale, Angelo (Singapore Journal of Legal Studies, 2016)
In this article I adopt a comparative law approach to illustrate the coexistence of various models governing the sale of goods, and their classification on the basis of two main characteristics: the transfer of property and the opposition certainty/flexibility. I use this approach to analyse the United Nations Convention on Contracts for the International Sale of Goods. 1 Then I examine how theCISG influenced several national systems and can influence future attempts at regional harmonisation. I conclude with the reasons that in my opinion make the CISG a good model for the sale of goods (prestige, equilibrium and derogability), and with the desirable future developments.

Réflexion critique sur l’attractivité du groupement d’intérêt économique (GIE) en droit de l’Organisation pour l’harmonisation du droit des affaires en Afrique (OHADA) - Dewedi, Éric (Les Cahiers de droit, 2016)
En droit de l’Organisation pour l’harmonisation du droit des affaires en Afrique (OHADA), la création du groupement d’intérêt économique (GIE) représente une opportunité laissée aux entreprises de mettre en commun leurs moyens pour accroître leurs activités économiques. Mais paradoxalement, le GIE n’est pas très utilisé par ses destinataires. Il fait ainsi l’objet d’un silence des acteurs qui conduit à s’interroger sur son attractivité. Il apparaît à l’analyse que l’un des attraits du GIE est voulu par la loi, mais qu’il est fortement compromis. En effet, les membres disposent d’une très grande liberté dans la constitution et le fonctionnement du GIE. Cette liberté n’a de limites que dans quelques règles impératives tournées vers la protection des tiers, notamment l’inopposabilité aux tiers des clauses limitatives des pouvoirs de l’adminsitrateur ou des administrateurs et la responsabilité indéfinie et solidaire des membres par rapport aux dettes du GIE. C’est cette responsabilité indéfinie et solidaire des membres relativement aux dettes du GIE qui compromet sérieusement l’attractivité de ce dernier. Il est cependant possible de rendre le GIE plus attractif par l’utilisation des conventions qui permettent à ses membres d’accorder des avantages particuliers aux nouveaux membres par contrat et aussi d’exclure la solidarité aux dettes par des accords avec les tiers contractants. Ces conventions pourraient assurer la sécurité du crédit par le recours aux garanties.

Teaching Transnational Commercial Law in the African Context - Eiselen, Sieg (University of Western Australia Law Review, 2016)

Les sociétés commerciales unipersonnelles du droit Bissau-Guinéen (acte uniforme relatif au droit des sociétés commerciales et du groupement d'intérêt économique de l'organisation pour l'harmonisation en Afrique du droit des affaires) - Espirito Santo, João (Revista da Faculdade de Direito da Universidade de Lisboa, 2016)
info:eu-repo/semantics/publishedVersion
Accepted: 2023-12-12T23:12:25Z
Keywords: Guiné-Bissau; OHADA; Sociedade unipessoal; Sociedades comerciais

La notion de bail professionnel en droit OHADA et ses implications sur la théorie générale du fonds de commerce - Eyango Djombi, André Desmonds (Juridical Tribune : Review of Comparative and International Law, 2016)
The last reform of the Uniform Act on General Commercial Law OHADA reconsidered several pieces of commercial law. The concept of leasing has not been spared. She, who was accompanied by the "commercial" substantive, has been transformed into "commercial lease". Question of style or simple semantics? Certainly not, because the legislature in 1997, had not previously dared revise the designation commercial lease that no longer fit with the extension of the beneficiaries he had devoted himself. With the reform of December 2010, the institution of the lease has just renamed. Parliament also confirmed the extension of the scope of economic actors involved in the protection of the lease. The regime of former Uniform Act was therefore not fully extended, particularly since we noted another significant change in the new text. Contrary to former Article 69 which devoted two cumulative criteria necessary for the implementation of the lease of the regime, including the situation in a populated city of more than 5,000 people and membership of local under lease to a designated class2, the new text retains a single criterion, that of belonging to a local specific category. This mutation disrupts some basics of goodwill theory. Indeed, with the increasing scope of lessees, there is a sliding protection to professional trader. This causes result in a substitution of the lease of the foundation that passes from customer to the profession. The loss of the privileged place of business customers coupled with doctrinal and jurisprudential developments in the theory of civil customers, argue for an assimilation of the different customer categories.
Keywords: Bail; Business assets; Business lease; Commercial Law; Fonds de commerce

L’apport épistémologique de la notion d’économie du contrat en matière d’interprétation - Fokou, Éric (Les Cahiers de droit, 2016)
La systématisation du contenu et des fonctions de la notion d’économie du contrat en droit français a abouti au postulat d’une théorie dite de l’économie du contrat. Dans son article, l’auteur tente d’en poser les jalons en dépassant l’approche dogmatique adoptée jusqu’ici par la doctrine française et belge. Il expose ainsi une nouvelle approche qui marque le passage de la notion à la théorie de l’économie du contrat en tant que théorie réaliste d’interprétation prenant en considération l’esprit général des clauses et la concrétisation de la volonté commune des parties d’après l’équilibre et la finalité de l’opération contractuelle. Cette théorie véhicule l’idée d’un contrat-opération qui se situe dans une perspective interdisciplinaire de l’analyse du phénomène contractuel, à contre-courant du modèle du contrat-obligation du Code Napoléon et du Code civil du Québec.

L’espace judiciaire pénal CEMAC : regard sur la déterritorialisation du droit pénal - Gatsi, Éric-Adol (Revue générale de droit, 2016)
Les enjeux liés à la lutte contre la criminalité transfrontalière et le raffermissement du Marché commun ont amené le législateur communautaire à jeter les bases d’un espace pénal commun dans la Communauté économique et monétaire des États de l’Afrique centrale (CEMAC). Intervenant dans un domaine où la souveraineté de l’État a longtemps été considérée comme un obstacle à toute harmonisation, la construction de l’espace pénal communautaire est perceptible sur les plans matériel et procédural. Sur le plan matériel, elle se manifeste par une communautarisation des règles pénales au moyen de l’institution d’infractions communautaires assorties de sanctions. Sur le plan procédural, la construction de l’espace pénal commun procède de la consécration, bien qu’imparfaite, du principe de la reconnaissance et de l’exécution mutuelles des décisions judiciaires en matière pénale, d’une part, et d’une procédure de coopération judiciaire qui emprunte progressivement la voie des organes communautaires, d’autre part.
Keywords: CEMAC; Coopération judiciaire; Espace pénal; Judicial co-operation; Penal space

Private Ordering of Exit in Limited Liability Companies: Theory and Evidence from Business Organization Contracts - Gomtsian, Suren (American Business Law Journal, 2016)
https://onlinelibrary.wiley.com/doi/10.1111/ablj.12087

The Admission and Enrolment of Foreign Legal Practitioners in South Africa under the Legal Practice Act: International Trade Law and Constitutional Perspectives - Hagenmeier, Cornelius; Shumba, Tapiwa; Mireku, Obeng (Potchefstroom Electronic Law Journal, 2016)
Globalisation requires ever closer co-operation between legal professionals hailing from different national jurisdictions. This interactive global environment has fostered growing international training and mobility among legal practitioners and the internationalisation of legal education. Increasing numbers of law students get trained in other countries as part of their undergraduate degrees or even come to foreign shores to obtain law degrees. Many students hailing from other African countries study towardsLLBdegrees at South African universities. Major commercial law firms ensure that they can offer in-house expertise on major foreign legal systems and co-operate with partner firms in other parts of the globe. The General Agreement on Trade in Services (GATS), to which South Africa is a party, is a multilateral agreement focusing on the liberalisation of trade in services amongst member countries. Services under the GATS system include legal services. The commitments made by South Africa under this agreement require that South Africa allows foreign legal practitioners to establish a commercial presence or be transferred to South Africa. The Bill of Rights entrenched in Chapter 2 of the South African Constitution guarantees fundamental rights including the right to equality and freedom of trade, occupation and profession. With the coming into force of the new Legal Practice Act 28 of 2014, which provides a legislative framework for regulating the affairs of legal practitioners, including their admission and enrolment, it is necessary to assess the extent to which the Act complies with the GATS rules and the South African Constitution. This paper examines the new Legal Practice Act 28 of 2014, and examines whether the Act addresses the conflicts that have always existed between the regulation of the legal profession and the admission of legal practitioners in South Africa with South Africa's commitments under the GATS system. Using the doctrinal legal method, it analyses and evaluates the rules governing the admission of foreign attorneys in South Africa from two perspectives. First, it considers them in the light of the international law obligations of the country and second it evaluates whether or not they comply with the South African Constitution, and more specifically with the Bill of Rights entrenched in the South African Constitution. While the new legislation may assist in ensuring the compliance of South Africa with the relevant GATS rules, it will depend on the regulations which still have to be promulgated to what extent the new legal framework will achieve the full compliance of South Africa with all relevant GATS rules. The paper concludes with recommendations for the reform of the Legal Practice Act. It argues that while the requirement to be a South African permanent resident in order to qualify for admission as an attorney may be justifiable in terms of GATS and in terms of South African constitutional law, it is not in South Africa's best interest to retain it. Consequently, the paper calls for the repeal of the permanent residence requirement for admission as an attorney in the county.
Keywords: Affirmative action; Designated groups; Employment equity; Equality; Minority group; Multi layered disadvantage; Situation sensitive

Arbitration and Justice Denial on Foreign Direct Investment - Hendrawan, Daniel (Indonesian Journal of International Law, 2016)
The economic growth in Indonesia is thrive. The Economic growth can not be separate of the role of investment in Indonesia. The population in Indonesia very much and also the location of the Indonesian state strategic pretty much made Indonesia enjoyed by citizens of Indonesia itself and also foreign nationals who wish to also invest in Indonesia. In Indonesia there is a domestic investment and foreign investment. In this paper will be devoted to foreign investment. Foreign investment that currently exist in Indonesia has a sizeable amount and spread from Sabang to Merauke, and also has sometimes caused the dispute. Dispute occurs either the foreign investment by government or also foreign investment with other parties outside the government well with other foreign investment, and also in the company itself. Foreign investment dispute settlement is not only done through the court owned by the government, but there are also ways of alternative dispute resolution outside the court . One of the alternative dispute resolution outside the court is Arbitration. Arbitration carried out as part of efforts to achieve settlement of the problem in terms of investment activity . Arbitration itself is set in the legislation applicable investment in Indonesia . The parties in capital investment may create a separate section in the agreement governing the settlement of disputes in the case of investments completed by Arbitration. In the event that the parties have arranged to settle the case with Arbitration, then the court is not allowed to try again or to interfere in the decision Arbitration. Arbitration is one of the solutions if justice denial occur in the settlement of foreign direct investment issue.
Keywords: Alternative; Arbitrage; Arbitragem; Arbitration; FDI; Foreign direct investment

Regional Powers and Leadership in Regional Institutions: Nigeria in ECOWAS and South Africa in SADC - Hulse, Merran (KFG The Transformative Power of Europe, 2016)
Regional powers are not always benevolent leaders when it comes to the building of regional institutions. While powerful states – particularly the “new” rising powers – may have a vested interest in regionalism as a means of projecting influence, regional powers may behave as coercive or benevolent leaders, or alternatively display an absence of leadership altogether. The drivers of varying regional power behavior can be attributed to their competing concerns regarding (economic) power, functional efficiency, international legitimacy, and neopatrimonial networks. This paper explores the varying behavior of Nigeria and South Africa in relation to the institutionalization of free trade areas and regional courts within their respective regions. Nigeria has displayed little leadership in ECOWAS trade integration due to domestic opposition; however, a newly-democratic Nigeria’s search for international legitimacy drove the establishment of the ECOWAS Court of Justice. Likewise, South Africa’s search for legitimacy drove its support for the SADC Tribunal, but the competing demands of different audiences led it to abandon this support. South Africa has also displayed leadership in relation to the SADC Free Trade Area; however, its neighbors perceive it as a self-interested, almost coercive actor. The findings suggest that the motivations for regional powers’ behavior vary across time and policy sectors, and that inconsistent behavior is driven by a change in the priority granted to different drivers.
Accepted: 2018-06-08T11:13:32Z https://refubium.fu-berlin.de/handle/fub188/21860

Foreign Direct Investments and Economic Growth of African Regions: A Comparative Study - Igbinosa, Sunday O.; Ikponmwosa, Noruwa Abu (UNILAG Journal of Humanities, 2016)
The paper examines the impact of Foreign Direct Investments (FDIs)on economic growth in the five regions of Africa, as well as identifies their respective drivers of growth. It employs the Ordinary Least Squares (OLS) multiple regression analysis to examine the relative impact of Foreign Direct Investments, balance of payments, trade openness, technology and quality of labour force on economic growth in each of the five regions between 1980 and 2012. The study finds that foreign Direct Investments (FDIs) have no significant impact on economic growth in the five regions of Africa. The impact of FDI on growth is positive in Eastern, Middle and Western Africa but negative in Northern and Southern Africa. Similarly, there are differentials in the drivers of growth in the five regions. While trade openness is a negative driver of growth in all regions of Africa except in Northern Africa, both balance of payments and quality of labour force have mixed impacts on economic growth in Africa. In addition, technological progress impacted growth in Middle, Southern Africa and Western Africa but it appears that lack of it retarded growth in Eastern and Northern Africa. The study calls for policy reform frameworks that encourage and boost foreign Direct Investment flows to all regions of Africa, particularly Direct Investments in critical sectors of the economies, as well as check the negative effects of foreign Direct Investments. Furthermore, it recommends that regional economic blocks in Africa should be resuscitated and supported to develop and promote intra-Africa trade and Investments.
Keywords: African regions; Drivers of growth; Economic growth; FDI; Foreign direct investment; Investments

Le contentieux de l’immatriculation du commerçant au registre du commerce et du crédit mobilier en droit OHADA - Kamnang Komguep, Irène Flore (Revue de droit de l'Université de Sherbrooke, 2016)
En droit des affaires, le commerçant est soumis à plusieurs obligations au rang desquelles figure l’immatriculation au RCCM. Celle-ci constitue une mesure de publicité légale dont l’accomplissement vaut, sauf exception, reconnaissance de la qualité de commerçant à l’égard de la personne physique et déclaration de la société commerciale à l’état civil. En plus de ces résultats immédiats, l’immatriculation a pour but d’assurer la sécurité des transactions commerciales. C’est à juste titre que le droit a prévu et organisé le contentieux de l’inexécution de l’obligation d’immatriculation et celui relatif aux incidents de la procédure d’immatriculation. La question qui se pose est celle de savoir si l’intervention du juge contribue effectivement à vaincre non seulement la négligence ou l’inertie des assujettis, mais aussi les obstacles à l’attribution d’un numéro d’immatriculation. Si l’organisation des différents axes du contentieux de l’immatriculation du commerçant au RCCM paraît satisfaisante, les suites de l’intervention du juge demeurent quant à elles perfectibles à certains égards. Il est nécessaire d’envisager des pistes de solutions tant en ce qui concerne le traitement du contentieux de l’inexécution de l’obligation d’immatriculation que celui des incidents de la procédure d’immatriculation.
Keywords: Crédit mobilier; Immatriculation; Registre du commerce

Pourquoi, en Afrique, « le droit » refuse-t-il toujours le pluralisme que le communautarisme induit ? - Le Roy, Étienne (Anthropologie et Sociétés, 2016)
Me posant cette question depuis une cinquantaine d’années, j’ai successivement écarté l’explication d’un simple laisser aller dans la reconduite de l’héritage colonial puis l’hypothèse d’une prétendue supériorité, jamais vérifiée autrement que dogmatiquement, du « droit moderne » sur la « coutume ancestrale ». Plus sérieuse fut l’explication liée à l’économie politique, un héritage marxien, et exigeant que les superstructures politiques et juridiques soient en phase avec l’insertion de l’Afrique dans le marché mondial. Mais, depuis ma participation à l’étude internationale sur les transferts de connaissances juridiques Nord-Sud, à la fin des années 1970, j’ai mis en évidence la place et le rôle de l’idéologie professionnelle des juristes et en particulier de leur philosophie spontanée idéaliste dont je dévoilerai ce qu’il masque à la lumière de mes travaux récents et selon le nouveau paradigme de la juridicité et de son pluralisme « intégral ». This question is focused on my research in the years 1960. After dismissing the continuity of policies such as bureaucratic carelessness of colonial inheritance and the hypothesis of a superiority of modern law facing to ancestral customs, I have debated an another inheritance, the Marxist one, about the link between the generalization of capitalism and legal and political superstructures. But an international project on legal transfers at the end of the 1970s’ revealed the place and role of a professional ideology, of the Lawyers, associated with technical training in law schools and enforcing monologism in the legal discourse. To escape to the effects of this ideology, we have to overhaul the analysis on the basis of the new paradigm of « juridicity » and of a « complete » pluralism.
Keywords: Colonization; Customs; Juridicity; Law and Anthropology; Legal Modernity; Marxism; Professional Ideology of Lawyers; anthropologie et droit; antropología y derecho; colonisation; colonización; costumbres; coutumes; ideología espontanea de los juristas; idéologie spontanée de juristes; juridicidad; juridicité; marxisme; marxismo; modernidad jurídica; modernité juridique

Contracts Governing the Use of Websites - Mik, Eliza (Singapore Journal of Legal Studies, 2016)
With the progressive transformation of the Internet from a romanticised instrument of freedom and self-expression into a commercial platform for digital distribution, most websites must be recognised as access interfaces to a wide range of content and services. This paper examines the contracts purportedly governing the use of such content and services. It explores the difficulties of establishing legal intention in a context that is not unambiguously commercial or transactional and contrasts popular beliefs with the basic principles of contract law. It draws a clear distinction between contracts governing traditional e-commerce exchanges, such as buying books on Amazon.com, and contracts governing the very use of websites. In the latter instance, the website (ie the resources made available thereon) constitutes the subject matter of the transaction. Equal importance must be attributed to the fact that such contracts are formed on websites and to the fact that they govern their use. The website user will question the existence of a contract on the basis that he did not have an intention to be legally bound, or had no awareness that a transaction was taking place. The website operator will argue that, objectively, all prerequisites of a legally enforceable agreement have been met. The outcome of the discussion will, to a large extent, depend on whether the user’s beliefs and expectations can be regarded as reasonable and on whether it is the user or the operator who deserves the protection of the objective theory of contract.

Réalités et perspectives du transport maritime conteneurisé et des installations portuaires en Afrique - Nachoui, Mostafa (Espace Géographique et Société Marocaine, 2016)
En Afrique, en plus des ports généraliers historiques et urbains, on voit émerger un nouveau réseau portuaire d'interfaces, sorte de plateformes de transbordement qui semble vouloir accompagner la révolution du conteneur. Ces ports sont loin des villes et ancrés à l’hinterland par un réseau de transport multimodal, avec leurs logiques de localisation et fonctionnement spécifiques. La mise en place de ce nouveau paysage portuaire a provoqué une véritable guerre des terminaux sur les côtes africaines. Chaque pays veut construire son Hub portuaire, d’où le bousculement des leaders mondiaux du transport maritime conteneurisé sur les côtes africaines. Certainement l’arrivée des opérateurs internationaux, améliorera aussi bien les infrastructures que les superstructures portuaires et leurs connexions et renforcera encore plus la productivité des ports, mais en même temps, pour certains, cela dépossède les africains de ces installations vitales et stratégiques; a déjà mis à mort successivement des compagnies maritimes africaines depuis le début du 21è siècle, et a totalement mis la main des opérateurs internationaux sur les ports africains par le système des concessions, idem pour les sociétés de manutention sur les trafics conteneurisés des grandes plateformes africaines. Au niveau des ports et du transport maritime international, différents pays et sociétés européennes dominent ce marché en Afrique, mais au il des ans, l’Europe est de plus en plus supplantée par la Chine et autres pays asiatiques comme partenaires des pays africains. La Chine, devenant très rapidement premier partenaire commercial de l’Afrique, s’élança dans des projets gigantesques de construction des ports, chemin de fer et autoroutes..., surtout en Afrique Orientale. Exemples, en Tanzanie le projet du port de Bagamoyo au Nord de Dar es-Salaam, susceptible de traiter 20 millions de conteneurs par an. Le projet Sud-Soudan-Ethiopie Transport Lamu Port(LAPSSET), inclus dans la Vision du Kenya 2030,Le projet du futur port en eau profonde d’El Hamdania à Cherchell dans la wilaya de Tipaza, en Algérie. Face à ces développements, Tout d’abord, les experts se demandent s’il y a un besoin bien réel dans ce domaine. Si oui, quels sont les ports qui pourraient jouer le rôle de Hub de transbordement continental et dans quel pays et qui gagnera les concessions?. Nous, on se demande même s’il n y a pas trop de projets? On se dit encore plus que les projets de Hubs en Afrique sont même plus nombreux pour un continent qui ne présente pas encore les caractéristiques d’un tel choix. Enfin, face aux développements des inventions technologiques rapides dans le domaine des constructions portuaires et portes conteneurs, et en vue des capacités financières et économiques réduites des pays africains, n’est-il pas légitime de se poser la question: Pourquoi cette course effrénée des pays africains à construire cette nouvelle génération des ports, très couteuse? et à se livrer une concurrence hasardeuse surement? Est-ce que le nouveau concept de port mobile qui vient d’apparaître avec une forte caution scientifique et technologie, mis au point par les chercheurs coréens du KAIST (Korean Advanced Institute for Science & Technology), ne remet pas en cause cette stratégie de construction des ports de transbordement en Afrique, en vue de ses nombreux avantages dont son coût réduit, sa protection de l’environnement avec notamment la réduction d’émanations de gaz, la sécurité et la réduction des délais de déploiement ?

La méthode conflictuelle dans le projet de code civil camerounais : contribution à la systématisation de l’évolution des méthodes en droit international privé - Ngono Nkoa, Véronique (Les Cahiers de droit, 2016)
La règle de conflit, qui a toujours été au coeur du droit international privé, a connu d’importantes transformations depuis quelques années. Considérée comme rigide, parce qu’elle est focalisée sur la localisation spatiale du rapport de droit, elle est devenue de plus en plus flexible et privilégie désormais la justice matérielle au détriment de la justice conflictuelle. Plus encore, elle a même été supplantée par la méthode de la reconnaissance. Cependant, le droit international privé camerounais est resté attaché à la méthode conflictuelle classique, alors qu’il serait nécessaire de prendre en considération toutes ces transformations qui ne sont pas sans incidences sur le développement du droit international privé.

Les déterminants de la disposition des managers à formaliser les PME informelles en Côte d’Ivoire - Nohoua, Traoré (Études caribéennes, 2016)
Cet article analyse les déterminants de la disposition des managers à formaliser les PME informelles en Côte d’Ivoire. Les données utilisées portent sur 400 entreprises du secteur informel enquêtées dans le cadre du projet CAPEC/CRDI¹. À partir des statistiques descriptives et de l’estimation d’un modèle Probit, l’étude met en évidence d’une part les variables qui influencent négativement et d’autre part celles qui influencent positivement la disposition à formaliser les PME. Il ressort de ces enquêtes que les taxes, le fait que l’entreprise soit dirigée par une femme, les coûts d’enregistrement, l’affiliation à une organisation politique et l’ignorance des procédures ont un effet négatif sur la disposition des managers à formaliser leurs entreprises. Les résultats montrent que la possession d’un plan d’affaires à la création, l’expérience du manager, la localisation, le niveau d’instruction supérieur, la simplification des procédures d’enregistrement affectent positivement la propension à formaliser les PME informelles. De même, les problèmes d’accès au financement et aux marchés publics conduisent les managers à la formalisation de leurs entreprises. Au regard de ces déterminants, la réduction des coûts de la formalisation, un meilleur accès des PME qui se formalisent au financement et aux marchés publics, le renforcement des capacités des opérateurs de l’informel, l’instauration d’une fiscalité incitative et la vulgarisation des procédures de déclaration s’avèrent des leviers importants de la formalisation. This paper analyzes the determinants of the willingness of managers to formalize informal SMEs in Côte d'Ivoire. The data used relate to 400 informal sector enterprises surveyed under the CAPEC / IDRC project. On the basis of descriptive statistics and the estimation of a Probit model, the study highlights both variables that negatively influence and those that positively influence the willingness to formalize SMEs. These surveys show that taxes, the fact that the company is headed by a woman, registration costs, affiliation to a political organization and ignorance of procedures have a negative effect on the formalization of businesses. Moreover, the results show that ownership of a business plan at creation, managerial experience, location, higher education, simplification of registration procedures positively affect the propensity to formalize informal SMEs. Similarly, the problems of access to finance and public procurement lead to more formalization. In view of these determinants, the reduction in the costs of formalization, better access by SMEs to financing and public procurement, capacity building for informal operators, the introduction of tax incentives and the Dissemination procedures are important levers of formalization.
The Determinants of the Willingness of Managers to Formalize Informal SMEs in Côte d'Ivoire
Keywords: Côte d'Ivoire; Formalisation; PME

Democracy and Accountable Governance in the SADC Region - Omede, Jolade; Akindola, Rufus; Ngwube, Arinze (African Journal of Politics and Administrative Studies, 2016)
The call for democracy worldwide is based on the assumption that it allows citizens involvement on how they are governed. Being a representative system of government, democracy is projected to make political leadership responsive and responsible to the entire citizenry of the state. Southern Africa region has the most animated economy in sub –Sahara Africa, and democratic ideals appear more firmly established in the region compared to other regions in Africa. This has made the region, among others in the continent, the preferred choice of many migrants from different parts of the world. It is believed that the region has reached its Eldorado. However, a close observation of the politics of that region tends to suggest there has been the institutionalization of democratic rule without commensurate enthronement of responsible and accountable governance. This study systematically examined the political configurations of the region to concretely determine how the practice of liberal democracy in the sub-region has translated to accountable and responsible governance and its overall impact of the living standard of the citizens of the countries of that region. The paper examined accountable governance in the sense that leaders will be able to mange resource of the state for the well being of the populace. The reverse has been the case for the region. Southern Africa needs a developmental and capable state for socio-economic progress and sustainable democracy. This cannot be achieved without responsible political leadership, which would be responsive to the yearnings of the people. The mode of analysis was based on secondary sources and observation method. The paper adopted secondary and observation techniques as the mode of analysis
Keywords: Accountability; Democracy; Development; Governance; Leadership

Les trois dimensions de la gouvernance coopérative agricole:Le cas des coopératives vinicoles du Languedoc-Roussillon - Saïsset, Louis-Antoine (Revue internationale de l'économie sociale, 2016)

International Trade, WTO and Economic Development - Siddiqui, Kalim (World Review of Political Economy, 2016)
This article examines the existing literature on trade liberalisation and its effect on the economies of developing countries. It will also briefly examine the theory of comparative advantage which is seen as justification for global trade liberalisation under the auspices of the World Trade Organization. This process is also associated with greater openness, economic interdependence and deepening economic integration with the world economy. The study is important because once again the international institutions strongly advocate trade and financial liberalisation in developing countries. The proponents of trade liberalisation argue that multilateral trade negotiations would achieve these goals, and poor countries particularly would benefit from it. However, such policies may increase vulnerability and make developing countries further hostages of international finance capital. Adoption of open market policies in agriculture would also mean the abandoning of self-reliance and food sovereignty, which may have wider consequences in terms of food shortages, food prices and rural employment.

Retour sur l'adaptation du droit au numérique - Sow, Djibril (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2016)
L'adaptation du droit au numérique apparaît comme une nécessité résultant de l‟essor considérable du numérique. Le numérique offre beaucoup d‟opportunités, mais engendre beaucoup de contraintes d‟ordre juridique. Une assez appréciable adaptation du droit au numérique est opérée par le législateur malien et les législateurs de certaines communautés sous régionales telles que l‟UEMOA, la CEDEAO et l‟OHADA. Cette adaptation est justifiée par la nécessité de donner aux acteurs les moyens de tirer profit du numérique avec une sécurisation juridique du cyberspace. Toutefois, elle doit être poursuivie afin de suivre l‟évolution rapide du numérique. The adaptation of the Law to digital is an necissity resulting at the big progress of the digital. The digital gives many opportunities, but creates so much diffuculties relating to law. Quite appréciable adaptation of malian law to the digital is done by national lawyer and lawyers of some communauties regarding Mali, such as WAMU, ECOWAS and OHADA. This adaptation is justified by the necessity to give the aims to use cyberspace and juridical security to the differents actors relating this space. But it must be continued in order to follow the evolution of the digital.
Keywords: Adaptation; Afrique de l'Ouest; Digital law; Droit du numérique; Mali; OHADA; UEMOA; West Africa

Due Process of Law in International Commercial Arbitration with Special Reference to Production of Documents - Zaheeruddin, Mohammed (Journal of Law and Criminal Justice, 2016)
Arbitration provides speedy mode of settlement of disputes between the parties. In the course of arbitration, the arbitration tribunal has an obligation to give a fair opportunity to the parties to present their case. The fair hearing or due process of law in arbitration requires that both parties must be treated equally and given opportunity to be heard, which include a party may request the other party for production of documents, which are relevant to the case. Hence, the international arbitration rules contained the provisions to order a party, on its own or on the request of a party, to produce the documents relevant to the outcome of the case. Unless otherwise agreed by the parties, any denial of this opportunity may be considered as a violation of due process of law, consequently a party may challenge the enforcement of the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Discovery; Due process of law; Production of document; UNCITRAL

Les spécificités de la règlementation bancaire au regard du droit OHADA des sociétés commerciales - Zerbo épouse Hien, Mariame (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2016)